Effects of crop cover on temperature regime of an alfisol in the tropics - Ghuman, B.S.; Lal, R. (1983)
Effect of maize (Zea mays L.) and cowpea (Vigna unguiculata L. Walp) canopies on the thermal regime of an Alfisol was investigated in flat and ridged seedbeds. An interaction was observed between canopy characteristics and soil moisture availability that influenced the soil temperature. When the soil moisture was >0.08 cm3 cm−3 (suction <0.64 bar), plants were protected against temporary wilting in the second half of the day and the 5-cm soil temperature decreased with an increase of maize and cowpea canopies. However, when the soil moisture was ≤0.0.8 cm3 cm−3 (observed on 53rd day after seeding of crops in 1980), the 5-cm maximum soil temperature under maize and cowpea crops was higher by 3 and 0.2°C, respectively, than in an uncropped flat seedbed, and by 7 and 3.9°C, respectively, than in uncropped ridges. The 5-cm soil temperature under maize was slightly lower in the early growth stages than under cowpea irrespective of the method of seedbed preparation. However, the reverse was true towards the crop's maturity. In addition to percent ground cover, soil moisture deficit, and the possible change in thermal conductivity were responsible for this reversal in soil temperature observed at the maturity stage. Soil temperature regime is strongly influenced by the interaction between canopy cover and soil moisture regime, on the one hand, and canopy height and density and wind velocity, on the other. The effect of increasing crop canopy on soil temperature on a given day (that provided an identical radiation for all plots) was studied for the flat seedbed by staggering the seeding dates of crops in the first season of 1981. On the 16th June (at approximately 50,40, and 20 days after seeding), and when the crops were not under moisture stress, an increase of maize canopy from 0 to 59.7% decreased the soil temperature range from 10.6 to 4.3°C at 1 cm and from 3.2 to 1.6°C at 20 cm depth. Similarly, an increase of cowpea cover from 0 to 100% decreased the temperature range from 10.6 to 1.7°C at 1 cm and from 3.2 to 0.6°C at 20 cm depth. Empirical models were developed that describe the effects of canopy cover, soil moisture, and radiation on maximum and mean soil temperatures at 1, 5, and 20 cm depths.